Evidence-Based Nursing Interventions for Postoperative Cancer Patients: A Systematic Review - gusya, winda (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2026)
Background: Cancer remains a leading cause of mortality worldwide, with surgical intervention being a primary treatment modality. Postoperative care is a critical phase that significantly influences patient recovery outcomes. Evidence-based nursing (EBN) has been recognized as an effective approach to improving postoperative care quality, yet no systematic review has specifically synthesized EBN interventions in the postoperative stage of cancer care. Objective: This study aims to systematically review and synthesize global evidence on evidence-based nursing interventions for postoperative cancer patients. Methods: A systematic review was conducted following PRISMA 2020 guidelines. Literature searches were performed across three databases — Scopus, PubMed, and Web of Science Core Collection — using Boolean search strategies. Studies published between 2015–2025, written in English, and focused on EBN interventions in postoperative oncology settings were included. Results: Fifteen studies met the inclusion criteria. Three major intervention categories were identified: (1) evidence-based nursing programs, (2) comprehensive/integrated nursing care, and (3) Enhanced Recovery After Surgery (ERAS)-based protocols. These interventions consistently demonstrated improvements in postoperative complication rates, psychological well-being, quality of life, functional recovery, length of hospital stay, and patient satisfaction. Conclusion: Evidence-based nursing interventions are effective in improving clinical and psychological outcomes among postoperative cancer patients. Integration of EBN into postoperative cancer care is essential and should be supported by targeted training and institutional commitment. Keywords: Evidence-based nursing, postoperative care, cancer, oncology, systematic review